Sticking to a plan: Adhesion and signaling control spatial organization of cells within migrating collectives - Macabenta, Frank (Curr Opin Genet Dev, 2019)
Collective cell migration is required in a vast array of biological phenomena, including organogenesis and embryonic development. The mechanisms that underlie collective cell migration involve not only the morphogenetic changes associated with single cell migration, but also require the maintenance of cell-cell junctions during movement. Additionally, cell shape changes and polarity must be coordinated in a multicellular manner in order to preserve directional movement in the migrating cohort, and often relates to multiple functions of common signaling pathways. In this review, we summarize the current understanding of the mechanisms underlying higher order tissue organization during migration, with particular focus on the interplay between cell adhesion and signaling that we propose can be tuned to support different types of collective movements.